Experience of parents regarding the care of their sons who developed coplications after traditional circumcision at a selected village in Sekhukhune district, Limpopo province - Ngunyulu, Roinah (University of Pretoria, 2026)
Dissertation (MSc)--University of Pretoria, 2018.